Vitamin K2 - Vital for Health and Wellbeing 2017
DOI: 10.5772/63712
|View full text |Cite
|
Sign up to set email alerts
|

Menaquinones, Bacteria, and Foods: Vitamin K2 in the Diet

Abstract: Vitamin K2 is a collection of isoprenologues that mostly originate from bacterial synthesis, also called menaquinones (MKs). Multiple bacterial species used as starter cultures for food fermentation are known to synthesize MK. Therefore, fermented food is the best source of vitamin K2. In the Western diet, dairy products are one of the best known and most commonly consumed group of fermented products.Although intensive research on metabolism and the biological effect of vitamin K2 continues today, data about v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 60 publications
(103 reference statements)
0
17
0
1
Order By: Relevance
“…Another interesting observation was the association of several Bacteroides species, such as B. ovatus, with a lean microbiota and observation of a positive correlation between Bacteroides and EDD, and an inverse correlation to glucose AUC. Bacteroides have a well characterized pathway to synthesize menaquinones (Vit K 2 ) 30 and it was recently demonstrated that the gut microbiota regulate endothelial function and blood pressure via a vitamin K 2 -dependent pathway. 31 It is interesting to speculate whether loss or reduction of bacterially-synthesized K 2 may have driven the results observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting observation was the association of several Bacteroides species, such as B. ovatus, with a lean microbiota and observation of a positive correlation between Bacteroides and EDD, and an inverse correlation to glucose AUC. Bacteroides have a well characterized pathway to synthesize menaquinones (Vit K 2 ) 30 and it was recently demonstrated that the gut microbiota regulate endothelial function and blood pressure via a vitamin K 2 -dependent pathway. 31 It is interesting to speculate whether loss or reduction of bacterially-synthesized K 2 may have driven the results observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria exert critical effects on the onset and perpetuation of gut inflammation in IBDs ( 125 ). The intestinal microorganism or bacteria present in food may produce bacterially synthesized menaquinones which contribute to K 2 requirements in human ( 126 ). Small-intestinal bacterial overgrowth (SIBO), associated with low circulating levels of K 2 ( 127 ), is involved in increased plasma levels of inactive MGP and results in alteration of K 2 metabolism ( 128 ).…”
Section: Vk In Intestinal Health and Diseasementioning
confidence: 99%
“…К основным источникам K 2 относят ферментированные продукты питания, мясо и молочные продукты. Основным способом обеспечения организма витамином К у здоровых людей является пищевой, так как снижение потребления витамина К с пищей не компенсируется кишечными менахинонами, что, вероятно, связано с лучшей биодоступностью филлохинона [31,32]. Вероятно, необходимый уровень поступления витамина К для сохранения соответствующей функции свёртывания крови у студентов достигается потребляемым набором продуктов [1,4,10,11], так как данные о дефиците этого витамина у здоровых взрослых отсутствуют.…”
Section: The Food Set Of Products Of Russian Students Depending On the Frequency Of Consumption лекции Lecturesunclassified